Bedside Assessment of Tissue Oxygen Saturation Monitoring in Critically Ill Adults: An Integrative Review of the Literature - Carol Diane Epstein; Karen Toby Haghenbeck (Critical Care Research and Practice)
Objective. Tissue oxygen saturation (StO2) monitoring is a noninvasive technology with the purpose of alerting the clinician of peripheral hypoperfusion and the onset of tissue hypoxia. This integrative review examines the rigor and quality of studies focusing on StO2 monitoring in adult critically ill patients. Background. Clinicians must rapidly assess adverse changes in tissue perfusion while minimizing potential complications associated with invasive monitoring. The noninvasive measurement of tissue oxygen saturation is based on near-infrared spectroscopy (NIRS), an optical method of illuminating chemical compounds which absorb, reflect, and scatter light directed at that compound. Methods. An integrative review was conducted to develop a context of greater understanding about complex topics. An Integrative review draws on multiple experimental and nonexperimental research methodologies. Results. Fourteen studies were graded at the C category. None reported the use of probability sampling or demonstrated a cause-and-effect relationship between StO2 values and patient outcomes. Conclusions. Future research should be based on rigorous methods of sampling and design in order to enhance the internal and external validity of the findings.